(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the age of digital change, mobile applications have emerged as significant educational tools, particularly for language acquisition. This article investigates how mobile apps can improve vocabulary retention in foreign language learners. It addresses the psychological and pedagogical components of mobile learning, introduces some of the most effective vocabulary apps, and assesses their influence using recent research.